LDL Lowering Properties Of Rutin In Diabetic Patients - MR.K.SATTANATHAN; DR.C.K.DHANAPAL; DR.R.MANAVALAN (International Journal of Pharma and Bio Sciences, 2010)
The objective of this study was to investigate the effect of Rutin supplementation Tablets in diabetic patients. This trial with 4 intervention periods within a gap of 15 days comprised 50 patients with type-II diabeties mellitus, 40-60 years old. These patients were supplemented with Rutin over the period of 60 days without altering their regular medications. Total Cholesterol (TCH), HDL, TGL, LDL and V-LDL were measured at baseline and after every 15 days i.e. on 15th, 30th, 45th & 60th days of Rutin supplementation. The same patients were stopped supplementing of Rutin for next 60 days and the investigation was carried out again at the end. HDL and TGL had showed a tendency of increase whereas LDL was considerably decreased. On the basis of these results it’s evident that Rutin supplementation Tablets can increase the LDL cholesterol lowering activity.